Optimization of Sea Transportation Services in The Kepulauan Seribu Using The Vehicle Routing Problem (VRP) Model - Darmadi, Darmadi; Soehodho, Sutanto; Nahry, Nahry (Smart City, 2026)
The Kepulauan Seribu regency relies heavily on sea transportation for passenger mobility and goods distribution. However, current systems face efficiency challenges, high operational costs, and potential imbalances between demand and service capacity. This study proposes a framework to optimize sea transportation services in the Kepulauan Seribu using the Vehicle Routing Problem (VRP) method, especially the Capacitated Vehicle Routing Problem – Many Single Depot (CVRP–MSD) model with heterogeneous fleets and mixed cargo (passenger and goods). The main objective is to minimize total operating costs, which include fixed costs of using the vessel and variable travel costs, and unmet demand, both passenger and goods. The model was formulated to determine the ideal number of ships to operate, design the most efficient shipping routes that connect depots in Jakarta with destination islands, address capacity limitations for passenger and goods transport, and minimize unmet demand. Analysis based on analogue studies shows that the application of the VRP model has the potential to significantly reduce transportation costs, increase fleet utilization, and provide quantitative data on service capacity shortages, thus allowing for better planning to meet the entire demand.